Students' Learning Needs Analysis in Learning English at SMAN 1 Campalagian Polewali Mandar - Bt Ibrahim, Hernawati; Nur, Rafiah; Ammade, Salasiah (STAIN Majene, 2023)
In SMAN 1 Campalagian, many students are not receiving an education that meets their diverse learning needs, as many teachers continue to use a